Inovasi Tata Kelola Pemerintah Dalam Meningkatkan Pendapatan Asli Desa ( studi kasus Gria Kuliner Bunderan ) - Desiana Reni Diyantasari; Wijaya, Dian; Muhaimin, Hikmah (Program Studi Ilmu Komunikasi Universitas Islam Majapahit, 2021)
This study aims to determine the innovation of village government governance in increasing village original income to advance the community and management of village revenue. Village government is a government organizer that is carried out by the village head assisted by village officials as an element of village government administration. The theory in this study uses the theory of Everett M. Rogers regarding innovation using qualitative descriptive research methods from the results of the research explaining that in village government governance in increasing the village's original income that is enumerated in Gria Kuliner Bunderan Pacet, it is implemented well by seeing the 5 indicators namely the relative advantages that exist in the advantages so that with the development of Gria Kuliner Pacet which brings many benefits so that there is development in Gria Kuliner Pacet, Second Compatibility is in a good presentation due to consistency in the village government in managing BUMDes, the three complexities are in the presentation in the sales process which already exists in the village government regulation, namely Gria Kuliner Bunderan Pacet, the four divisibility is on a good presentation due to an experiment in the management of the BUMDes Gria culinary roundabout to be used as a tourist spot culinary, the Fifth Communicability is in a good presentation and can be published to the community where the results of the innovations produced by the village government are in the form of pacet bunderan culinary gria which can improve the community's economy with the existence of BUMDes in the form of a vegetable market that gets suppliers from local residents.So the results of research from the data obtained by researchers can be concluded that regarding the Roundabout Culinary Griya there is a development as seen from the management system.